STRATEGI INVESTASI CERDAS UNTUK MENINGKATKAN PEMAHAMAN INVESTASI GENERASI Z - Masithah Akbar; Yanuar Bachtiar; Rizky Nastiti; R.R. Siti Munawaroh; Norbaiti Norbaiti; Stephanus Julianto Lexta Dwitia; Nadya Fitriany; Kezia Setiawan; I Komang Sumerta (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2023)
Lack of understanding of the importance of good and safe financial planning and management is one of the reasons for the lack of participation of the younger generation in investing in stocks. Therefore, this seminar was carried out in order to increase the awareness of the younger generation, especially generation Z, on the importance of easy and safe investment. Through the introduction of the Smart Investment Strategy, participants are expected to be able to invest in stocks intelligently, especially in the capital market. This activity was attended by 52 students from various higher education institutions in Banjarmasin. The results of this activity are expected to encourage students to invest in stocks safely so that they can plan and manage their finances better.